Green image implication towards customer satisfaction and customer loyalty in the Malaysian hotel industry - Yusnita, Yusof; Yahaya, Ibrahim; Zainudin, Awang (2017)
Tourism is currently one of the largest sectors in the world and has contributed to world economic growth. Malaysia, in recent times, has become one of the most visited countries in Southeast Asia. An increase of tourist arrivals (from both domestic and international visitors) has caused an increase in the number of accommodation that is available each year, and placesthe hotel industry as one of the most popular segments in the tourism industry. Since environmental awareness has been increasing across the world, a green image is seen to be an important aspect to be explored in the hotel industry in current times. Thus, the aim of this study is to examine the influence of a green image towards customer satisfaction and customer loyalty among a hotel’s guests in the Malaysian hotel industry.